2016
DOI: 10.1080/14779072.2016.1247694
|View full text |Cite
|
Sign up to set email alerts
|

Advanced heart failure: an appraisal of the potential of levosimendan in this end-stage scenario and some related ethical considerations

Abstract: The later stages of heart failure are characterized by a steady decline in quality of life. Clinical priorities should be to maintain functional capacity and quality of life. In the absence of sufficient organs for transplantation, options include left ventricular assist devices and inotropic support. Areas covered: We examined data published in the last two decades on the use of inotropes and inodilators in advanced heart failure. Expert commentary: In the literature, use of conventional inotropes, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 113 publications
(124 reference statements)
1
14
0
Order By: Relevance
“…Patients with advanced HF need frequent hospitalizations and present a very poor quality of life [6]. In the PARADIGM-HF trial, only 60 patients in NYHA class IV (advanced HF) were included, and for these patients the benefits of sacubitril/valsartan were consistent with the findings in the whole study population [5]. …”
Section: Clinical Commentsupporting
confidence: 67%
See 1 more Smart Citation
“…Patients with advanced HF need frequent hospitalizations and present a very poor quality of life [6]. In the PARADIGM-HF trial, only 60 patients in NYHA class IV (advanced HF) were included, and for these patients the benefits of sacubitril/valsartan were consistent with the findings in the whole study population [5]. …”
Section: Clinical Commentsupporting
confidence: 67%
“…Moreover, due to numerous comorbidities often present in these patients, transplantation and left ventricular assist devices are often not suitable in clinical practice [5]. In this challenging setting, administration of inotropic agents often remains the only possible therapy; however, this treatment requires frequent hospitalizations [5]. …”
Section: Introductionmentioning
confidence: 99%
“…31 However, this agent has not shown any benefit in randomised controlled trials in terms of resolution of symptoms and improvements in ventricular function. 32 A more recent, non-randomised prospective study has suggested a potential benefit for anti-tumour necrosis factor α therapy with pentoxyfylline 33 although trends have not yet been corroborated in more established studies.…”
Section: Current Researchmentioning
confidence: 99%
“…In particular, the intermittent use of i.v. levosimendan in chronic AdHF has been suggested to prevent acute decompensation and frequent rehospitalization, and possibly to improve other outcomes [15].…”
mentioning
confidence: 99%
“…A, recovery after first episode followed by stable period of variable length; B, non-surviving the first episode; C, poor recovery after first episode followed by deterioration; D, ongoing deterioration with intermittent crises (advanced heart failure) and unpredictable death point. indicated for HF, and multiple meta-analyses have shown possible advantages of levosimendan in various clinical settings [15][16][17][18]. In particular, the intermittent use of i.v.…”
mentioning
confidence: 99%